Endogenous markups and fiscal policy - Costa, Luís F. (2010)
This note analyses a simple imperfectly competitive general equilibrium model where the entry mechanism generates an endogenous markup. In this second-best world fiscal policy is more effective than in Walrasian or in fixed-markup monopolistic competition models, as it produces efficiency gains through entry.